234 Clonality analysis of synchronous endometrial and ovarian carcinomas in patients with lynch syndrome. (18th September 2019) - Moukarzel, L; Da Cruz Paula, A; Hoang, T; Sebastiao, AP; Pareja, F; Park, K; Jungbluth, A; Capella, G; Pineda, M; Reis-Filho, J; Abu-Rustum, N; Levin, J; et al.
Abstract : Objectives: Sporadic synchronous endometrial (ECs) and ovarian cancers (OCs) have been shown to be clonally-related and to likely constitute metastases from each other. We sought to define whether synchronous ECs/OCs in patients with Lynch syndrome would be clonally-related or independent tumors. Methods: We subjected synchronous ECs/OCs from four patients with clinically confirmed Lynch syndrome to massively parallel sequencing targeting 468 cancer-related genes. Somatic mutations, copy number alterations, clonal relatedness and clonal decomposition were performed using state-of-the-art bioinformatics methods. Results: All synchronous ECs/OCs were considered independent primaries based on clinico-pathologic criteria. Sequencing analysis revealed that the ECs and OCs of three cases harbored strikingly similar repertoires of somatic mutations and gene copy number alterations and were clonally related. Specifically, in one case (LS2), a subset of subclonal mutations in the EC became clonal in the OC, suggesting that the ovarian tumor originated from the endometrial tumor. In contrast, in another case (LS5), the EC and OC harbored distinct somatic mutation profiles with no shared mutations; consistent with them constituting two independent primary tumors. In this case (LS5), a PTEN mutation and loss of protein expression were found to be restricted to the EC. Conclusions: Akin to sporadic synchronous ECs/OCs, the majority of Lynch syndrome-related synchronous ECs/OCs originate from a single primary tumor at variance with their clinical-pathologic diagnosis. Given that in the context of Lynch syndrome, synchronous ECs/OCs may be independent primary tumors, Lynch syndrome testing should be considered when synchronous ECs/OCs present with distinct genetic or immunohistochemical profiles.